Characterization of uronate dehydrogenases catalysing the initial step in an oxidative pathway. Issue 4 (17th April 2015) - Pick, André; Schmid, Jochen; Sieber, Volker
Summary Uronate dehydrogenases catalyse the oxidation of uronic acids to aldaric acids, which represent 'top value‐added chemicals' that have the potential to substitute petroleum‐derived chemicals. The identification and annotation of three uronate dehydrogenases derived from Fulvimarina pelagi HTCC2506, Streptomyces viridochromogenes DSM 40736 and Oceanicola granulosus DSM 15982 via sequence analysis is described. Characterization and comparison with two known uronate dehydrogenases in regard to substrate spectrum, catalytic activity and pH as well as temperature dependence was performed. The catalytic efficiency was investigated in two different buffer systems; potassium phosphate and Tris‐HCl. In addition to the typical and well available substrates glucuronate and galacturonate also mannuronate as part of many structural polysaccharides were tested. The uronate dehydrogenase of Agrobacterium tumefaciens and Pseudomonas syringae showed catalytic dependency on the buffer system resulting in an increased Km especially for glucuronate in potassium phosphate compared with Tris‐HCl buffer. Enzyme stability at 37°C of the different Udhs was in the order: P. syringae < S. viridochromogens < A. tumefaciens < F. pelagi < O. granulosus. All enzymes showed activity within a broad pH range from 7.0 to 9.5, only O. granulosus had a very narrow range around 7.0.